Progress in Personalizing Chemotherapy for Bladder Cancer - James S. Chang; Primo N. Lara; Chong-Xian Pan (Advances in Urology)
Platinum-based chemotherapy is commonly used for the treatment of locally advanced and metastatic bladder cancer. However, there are currently no methods to predict chemotherapy response in this disease setting. A better understanding of the biology of bladder cancer has led to developments of molecular biomarkers that may help guide clinical decision making. These biomarkers, while promising, have not yet been validated in prospective trials and are not ready for clinical applications. As alkylating agents, platinum drugs kill cancer cells mainly through induction of DNA damage. A microdosing approach is currently being tested to determine if chemoresistance can be identified by measuring platinum-induced DNA damage using highly sensitive accelerator mass spectrometry technology. The hope is that these emerging strategies will help pave the road towards personalized therapy in advanced bladder cancer.